2021
DOI: 10.3389/fmolb.2021.621128
|View full text |Cite
|
Sign up to set email alerts
|

Integrating an Enhanced Sampling Method and Small-Angle X-Ray Scattering to Study Intrinsically Disordered Proteins

Abstract: Intrinsically disordered proteins (IDPs) have been paid more and more attention over the past decades because they are involved in a multitude of crucial biological functions. Despite their functional importance, IDPs are generally difficult to investigate because they are very flexible and lack stable structures. Computer simulation may serve as a useful tool in studying IDPs. With the development of computer software and hardware, computational methods, such as molecular dynamics (MD) simulations, are popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…After we obtained the above information about the binding patterns between hMEX3B and its RNA substrate, we tried to generate the structural model of the KH1/2-12-nt RNA by molecular dynamics (MD) simulation methods. Different from conventional MD simulation, integrative modeling combines an enhanced sampling method and experimental data such as SAXS to efficiently sample the conformations of the apo form and complex proteins 24 . During the simulation of the KH1/2 apo form, we found that χ2 decreases relatively fast in the first five cycles and then slowly converges to approximately 1.0 after the 5th cycle (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After we obtained the above information about the binding patterns between hMEX3B and its RNA substrate, we tried to generate the structural model of the KH1/2-12-nt RNA by molecular dynamics (MD) simulation methods. Different from conventional MD simulation, integrative modeling combines an enhanced sampling method and experimental data such as SAXS to efficiently sample the conformations of the apo form and complex proteins 24 . During the simulation of the KH1/2 apo form, we found that χ2 decreases relatively fast in the first five cycles and then slowly converges to approximately 1.0 after the 5th cycle (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 ). However, extensive simulations and experimental techniques that are commonly used to probe IDRs ( Robustelli et al, 2020 ; Chang et al, 2021 ; Ding et al, 2021 ) are best suited for much smaller proteins. Therefore, many studies of intact MAPIDs are limited by the large number of disordered residues, as well as the likely presence of multiple disordered regions within a single protein.…”
Section: Myofilament-associated Protein With Intrinsic Disorder (Mapid)smentioning
confidence: 99%